MODELING USING REGRESSION ANALYSIS OF SONOGRAPHIC PARAMETERS OF KIDNEYS DEPENDING ON THE FEATURES OF THE SIZE OF PRACTICAL HEALTHY WOMEN WITH MESOMORPHIC SOMATOTYPE - Черкасов, В.Г.; Устименко, О.С. (World of Medicine and Biology, 2017)
Aim of our work – to construct and analyze the regression models of individual sonographic sizes of right and left kidneys in practically healthy women of mesomorphic somatotype depending on the features of anthropometric and somatotypological indicators.Materials and methodsWithin the framework of the agreement on scientific cooperation from the database of the research center of the Vinnitsa National Medical University named after Pirogov taken the primary sonographic parameters and anthropometric indices of 121 practically healthy women (from 22 to 35 years old) of the first mature age who live in the third generation in Podillia.All of them had an anthropometric survey conducted by Bunak in the modification of Shaporenko. The evaluation of the somatotype was carried out according to the mathematical scheme of J. Carter and B. Heath. Determination of the absolute amount of fat, bone and muscle mass components of the body was calculated according to the formulas J. Matiegka, as well as the muscular component - according to the formulas of the American Institute of Nutrition.Sonography of the right and left kidneys was performed using the ultrasound diagnostic system "CAPASEE" SSA-220A (Toshiba, Japan) with a 3.75 MHz convective sensor and Voluson 730 Pro diagnostic ultrasound system (Austria), a 4-10 MHz convective sensor. For each kidney the length, width (transverse size) and the anterior-posterior dimensions were determined; the area of the longitudinal and transverse sections of the kidneys and their sinuses, as well as the volume of the right and left kidneys.To construct models of individual sonographic parameters of the kidneys, the method of stepwise regression analysis in the package "STATISTICA 6.1" was used.Results. DiscussionsAs a result of the survey of 45 practically healthy women Podillia region of Ukraine mesomorphic somatotype built significant regression models sonographic parameters of right and left kidneys depending on anthropometric and somatic parameters with coefficient of determination (R2) greater than 0.6. Of the 16 possible sonographic parameters of kidneys built only 7 significant regression models (namely, the length and width of the left kidney in the longitudinal section, the anterior-posterior size of the left kidney on the transverse section, the area of the longitudinal section and the volume of the left kidney and the area of the cross-section of the sinus and volume of the right kidney) with R2 from 0.607 to 0.641. Sonographic parameters built models both kidneys often include - girth body size (29.8%) and cellophane indicators (19.1%); and among individual anthropo-somatotypological indicators - the largest head length and body weight (up to 4 models) and the circumference of the foot, the thickness of the skin-fat fold on the anterior surface of the shoulder and the muscle mass of the body, determined by the formula of the American Institute of Nutrition (up to 3 models)The obtained results indicate the expediency of further introduction into medical modeling of individual sonographic parameters of the kidneys, depending on the anthropometric and somatotypological parameters, with due consideration of the peculiarities of the body structure. This will ensure an adequate interpretation of sonographic indicators of the kidneys, will allow to predict the course of pathological processes and choose optimal operational and technical solutions.
Keywords: kidneys; sonography; anthropometry; somatotype; virtually healthy women; regression analysis